"The margin for error": Ritual coping with cultural pressures - Broch, T. B.; Kristiansen, E (Scandinavian Journal of Medicine & Science in Sports, 2014)
Meritocratic sport cultures, media attention, coaches' ambitions, and "enthused" parents create stress and make coping pivotal for athletes' performance. A transdisciplinary dialogue between a sports-sociologist and a sport-psychologist manifests ritual practices in athletes' lived sport experiences as coping strategies. Based on two empirical strands, field observations of boy's handball and interviews with elite male wrestlers', analysis of pregame routines scrutinize psychosocial dimensions of athletes' ritual practice. The implications of ritual meaning making are investigated as a means to cope with sport specific sociocultural anxieties. Rituals are interpreted as psychosocial processes applied to construct perceived order and comfort in stressful sport milieus. We contend that it is reasonable to believe that successful coping is not solely because of athletes' psychological competencies and experiences, but also their ability to ritually use culture in meaningful ways. To manifest important contextual aspects of athletes' lived sport experiences, to nurture task-oriented sport milieus, and to create change in sport and physical cultural contexts, we consequently suggest that the cultural meanings applied in ritual should be an important aspect to address.